PENGARUH PEMANFAATAN SISTEM INFORMASI AKADEMIK BERBASIS WEB DAN MOBILE TERHADAP KEPUASAN DAN KINERJA MAHASISWA (STUDI PADA STMIK MULTICOM KOTAMOBAGU - Supit Mamuayat; Agung Yuliyanto Nugroho; Fitly Tjong Mamuaya (Smart Education, 2026)
This study aims to examine the effect of the utilization of web- and mobile-based academic information systems on student satisfaction and academic performance at Sekolah Tinggi Manajemen Informatika dan Komputer (STMIK) Multicom Kotamobagu. The rapid advancement of information technology has encouraged higher education institutions to adopt digital systems to enhance the efficiency, accessibility, and quality of academic services. However, the effectiveness of such systems in improving student satisfaction and performance still requires empirical validation. This research employs a quantitative approach using a survey method. The population consists of active students at STMIK Multicom Kotamobagu, while the sample is determined using purposive sampling, focusing on students who have utilized the academic information system. Data were collected through structured questionnaires using a Likert scale. The data analysis technique applied in this study is Structural Equation Modeling based on Partial Least Squares (SEM-PLS), which allows for the simultaneous examination of relationships among variables. The independent variable in this study is the utilization of the academic information system, while the dependent variables include student satisfaction and academic performance. The findings reveal that the utilization of web- and mobile-based academic information systems has a positive and significant effect on student satisfaction. Furthermore, the system utilization also significantly influences student performance, both directly and indirectly through satisfaction as a mediating variable. These results indicate that an accessible, user-friendly, and responsive academic information system can enhance user experience and support improved academic outcomes. This study provides practical implications for higher education institutions in optimizing digital academic systems. Improving system quality, usability, and real-time information delivery is essential to enhance student satisfaction and performance sustainably.